JOINT VENTURE EDUCATION - Fathoni, Abdullah; Yosepha, Sri Yanthy (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2024)
Empirical research shows that one of the problems of Unsurya students is the cost aspect and one of the operational problems at Halim Airport is organizational staffing or the HR aspect. Systematic writing, first an empirical study with objects such as the Solar Elements and Halim Airport. Second, analysis in the field or field study. Third, library Study. Fourth, study of solutions and study of script writing. The big conclusion of this text is that there is a joint solution between Unsurya and Halim Airport with a mutualistic relationship based on the concept of "Joint Venture Education"